Klebsiella pneumoniae capsule polysaccharide as a target for therapeutics and vaccines - Opoku-Temeng, Clement (Comput Struct Biotechnol J, 2019)
Carbapenem-resistant (CR) Klebsiella pneumoniae has emerged as an urgent public health threat in many industrialized countries worldwide, including the United States. Infections caused by CR K. pneumoniae are difficult to treat because these organisms are typically resistant to multiple antibiotics, and the patients have significant comorbidities. Notably, there is high (∼50%) mortality among individuals with bacteremia caused by CR K. pneumoniae. Given the dearth of new antibiotics, and the recent convergence of multidrug resistance and hypervirulence, there is a critical need for alternative strategies for the treatment of CR K. pneumoniae infections. The capsule polysaccharide (CPS) of K. pneumoniae has long been viewed as an important virulence factor that promotes resistance to phagocytosis and serum bactericidal activity. Thus, the CPS has been targeted previously for the development of therapeutics and vaccines, although there is no licensed CPS-based vaccine or therapy for the treatment of CR K. pneumoniae infections. Here, we discuss immunoprophylactic and immunotherapeutic approaches that have been tested previously for the treatment of Klebsiella infections. We also suggest potential strategies to promote development of CPS-based vaccines and therapies for prevention and treatment of CR K. pneumoniae infections.